The development of service user‐led recommendations for health and social care services on leaving hospital with memory loss or dementia – the SHARED study. (8th July 2016) - Mockford, Carole; Seers, Kate; Murray, Matt; Oyebode, Jan; Clarke, Rosemary; Staniszewska, Sophie; Suleman, Rashida; Boex, Sue; Diment, Yvonne; Grant, Richard; Leach, Jim; Sharma, Uma
Abstract: Background: Health and social care services are under strain providing care in the community particularly at hospital discharge. Patient and carer experiences can inform and shape services. Objective: To develop service user‐led recommendations enabling smooth transition for people living with memory loss from acute hospital to community. Design: Lead and co‐researchers conducted semi‐structured interviews with 15 pairs of carers and patients with memory loss at discharge, 6 and 12 weeks post‐discharge and one semi‐structured interview with health and social care professionals and Admiral Nurses. Framework analysis was guided by co‐researchers. Two focus groups of study participants, facilitated by co‐researchers, met to shape and finalize recommendations. Setting and participants: Recruitment took place in acute hospitals in two National Health Service (NHS) Trusts in England. Patients were aged 65 and over, with memory loss, an in‐patient for at least 1 week returning to the community, who had a carer consenting to be in the study. Results: Poor delivery of services caused considerable stress to some study families living with memory loss. Three key recommendations included a need for a written, mutually agreed discharge plan, a named coordinator of services, and improved domiciliary care services. Discussion and conclusions: Vulnerable patients with memory loss find coming out of hospital after an extended period a stressful experience. The SHARED study contributes to understanding the hospital discharge process through the eyes of the patient and carer living with memory loss and has the potential to contribute to more efficient use of resources and to improving health outcomes in communities.